Neuronal synchronization without calcium-dependent synaptic transmission in the hypothalamus. - Bouskila, Y (1993)
A critical question in understanding the mammalian brain is how populations of neurons become synchronized. This is particularly important for the neurons and neuroendocrine cells of the hypothalamus, which are activated synchronously to control endocrine glands and the autonomic nervous system. It is widely accepted that communication between neurons of the adult mammalian brain is mediated primarily by Ca(2+)-dependent synaptic transmission. Here we report that synchronous neuronal activity can occur in the hypothalamic suprachiasmatic nucleus without active Ca(2+)-dependent synaptic transmission. Simultaneous extracellular recordings of neuronal activity in the suprachiasmatic nucleus, which contains the mammalian biological clock, confirmed a circadian rhythm of synchronized activity in hypothalamic slices. Ca(2+)-free medium, which blocks chemical synaptic transmission and increases membrane excitability, produced periodic and synchronized bursts of action potentials in a large population of suprachiasmatic nucleus neurons with diverse firing patterns. N-Methyl-D-aspartic acid, non-N-methyl-D-aspartic acid, and gamma-aminobutyric acid type A receptor antagonists had no effect on burst synchrony. Whole-cell patch-clamp recordings confirmed that the Ca(2+)-free solution blocked evoked postsynaptic potentials and that the mixture of antagonists blocked the remaining spontaneous postsynaptic potentials. Therefore, mechanisms other than Ca(2+)-dependent synaptic transmission can synchronize neurons in the mammalian hypothalamus and may be important wherever neuronal networks are synchronized.